(untitled) (Archives of Mechanics - Test, 2004)
The paper in which Maksymilian Tytus Huber formulated his known yield criterion and strength hypothesis appeared in print precisely one century ago and was published, unfortunately only in Polish. It was a new idea, since for the first time it was not only assumed but also published that the measure of the material effort might depend on the spatial state of stresses, not on a single component of stress tensor. With time, and the results of new experiments, Huber’s idea became popular abroad, particularly after citations by A. and L. Föppls in their known monographs.